(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
From egg batches of Thaumetopoea pityocampa (Den. & Schiff.) collected on the lberian Peninsula 5.4 -10.4% males of the egg parasitoid Ooencyrtus pityocampae (Mercet) emerged and copulated under laboratory conditions: Thus, copulation of the species could be studied in detail. For producing obspring, eggs of Bombyx mori L. and T. pityocampa were used. Mated females of the encyrtid produced only female offspring, since from eggs of virgin females both sexes developed. The honey-fed females lived maximally 56 days and laid 70 eggs per female at maximum. From 59% of the eggs laid female offspring emerged after 21 days. About 11, maximally 38, offspring individuals per female were observed. Totally, in 668 offspring specimens the male part was 2.7%. The diapausing individuals were not considered.